IMPACT OF NIGERIA AGRICULTURE PROMOTION POLICY ON THE TECHNICAL EFFICIENCY AND INCOME OF SMALL- SCALE PALM OIL PROCESSORS IN EDO STATE - Ijie, Ben Asuelimen (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2023)
The Nigeria Agriculture Promotion Policy (APP) aimed to enhance agricultural productivity and increase the income of actors along the agriculture value chain. Its four priority goals are to create employment, increase foreign exchange earnings, achieve economic diversification, and achieve food security. This study assesses the contributions of the Agriculture Promotion Policy (APP) to the income and technical competencies of small-scale palm oil processors/millers in Edo State. Employing a mixed-methods approach, fifty-five (55) palm oil processors from eleven (11) local government areas across three (3) senatorial districts of Edo State were surveyed. Quantitative data were gathered through questionnaires and subjected to descriptive statistical analysis. Concurrently, qualitative data were gathered via key informant interviews and analysed using thematic analysis. Results indicate that the APP was effective in bolstering technology adoption and yield/output performance for palm oil processors/millers. Notably, the income of processors/millers increased by 40.1%, ascending from N1,510,464.80 in 2015 (pre-APP) to N2,115,988.92 in 2021 (after APP implementation). However, certain limitations surfaced reflective of inadequate access to loans for procuring advanced palm oil production machinery. To optimize the policy's impact, it is recommended that the government introduce regular training programs for processors/millers and facilitate their access to loans for acquiring efficient palm oil processing equipment. These findings hold significant implications for Nigerian agricultural policy development. While the APP has substantiated its efficacy in boosting small-scale palm oil productivity, addressing the identified policy limitations is imperative for maximizing its overarching goals.